PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN DI KOTA BANGKINANG - Yaniria Laoli; Samsurijal Hasan (STIE Bangkinang Publishing, 2020)
This research was conducted with the aim to test product quality, price and promotion of purchasing decisions and variables that influence purchasing decisions of bottled drinking water in the Aqua and Le-Minerale brands in Bangkinang City. The population in this study were all consumers who made the decision to purchase bottled water Aqua and Le-minerale in Bangkinang City. The technique used in sampling is purposive sampling. The sample in this study were selected as many as 100 people. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 25.00 for windows. The results of the study showed that simultaneous bottling of Aqua had a significant effect on purchasing decisions, whereas bottled drinking water simultaneously had no significant effect on purchasing decisions. Partially, product quality and price have a significant effect on purchasing decisions, while promotion variables have no effect on purchasing decisions.